PENGARUH TRISILA TNI AL TERHADAP PEMBENTUKAN SUMBER DAYA MANUSIA UNGGUL PRAJURIT DINAS PEMELIHARAAN DAN PERBAIKAN KAPAL KOMANDO ARMADA II - Teguh Setiyawan; Yohanes (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar, 2021)
Along with the development of science and technology that has led to glob-alization, the relevance of the Indonesian Navy Trisila is again tested in encour-aging the formation of excellent human resources (HR) for its soldiers. This study aims to analyze the influence of Military Discipline, Hierarchy and Hon-or as elements in the TNI AL Trisila on the formation of superior human re-sources for Satker